Role of magnesium sulphate in the treatment of hypomagnesaemia in eclamptic patients - Anwary, SA; Alfazzaman, M; Islam, MR (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 252-256 The abstract of this article is available on the PubMed website